2013
DOI: 10.1007/s00428-013-1457-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromophobe renal cell carcinoma—chromosomal aberration variability and its relation to Paner grading system: an array CGH and FISH analysis of 37 cases

Abstract: Genetically, chromophobe renal cell carcinoma (ChRCC) is characterized by multiple chromosomal changes, especially losses. The most common losses include chromosomes 1, 2, 6, 10, 13, 17, and 21. The Fuhrman grading system lacks prognostic relevance for ChRCC, and recently, a new grading system for ChRCC was proposed by Paner. The objective of this study was to map the spectrum of chromosomal aberrations (extent and location) in a large cohort of ChRCCs and relate these findings to the Paner grading system (PGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…In their study, one of the most comprehensive ever undertaken on ChrRCC, the remaining 62 of 66 ChrRCC cases (which also included 19 eosinophilic ChrRCC), demonstrated a classic karyotype profile of ChrRCC, with frequent multiple losses of chromosomes 1, 2, 6, 10, 13 and 17 (in 86% of cases) and less common losses of chromosomes 3, 5, 8, 9, 11, 18 and 21 (in 12–58% of cases). In some studies, however, a combination of chromosomal losses and gains have been found in usual ChrRCC . To our knowledge, the only other study that included similar tumours to the LOT described herein was conducted by Kuroda et al .…”
Section: Discussionmentioning
confidence: 88%
“…In their study, one of the most comprehensive ever undertaken on ChrRCC, the remaining 62 of 66 ChrRCC cases (which also included 19 eosinophilic ChrRCC), demonstrated a classic karyotype profile of ChrRCC, with frequent multiple losses of chromosomes 1, 2, 6, 10, 13 and 17 (in 86% of cases) and less common losses of chromosomes 3, 5, 8, 9, 11, 18 and 21 (in 12–58% of cases). In some studies, however, a combination of chromosomal losses and gains have been found in usual ChrRCC . To our knowledge, the only other study that included similar tumours to the LOT described herein was conducted by Kuroda et al .…”
Section: Discussionmentioning
confidence: 88%
“…Renal tumors characterized by multiple losses are traditionally designated as chromophobe RCC, with losses frequently involving chromosomes 1, 2, 6, 10, 13, 17, and 21 [1]. However, recent studies have revealed a wider spectrum of chromosomal abnormalities including not only multiple losses but also numerous gains [11,18,19]. From the genetic point of view, one may speculate the existence of a histogenetic link between MTSRCC and CHRCC.…”
Section: Discussionmentioning
confidence: 97%
“…The procedures of DNA purification, integrity control, array CGH, and fluorescent in situ hybridization (FISH) analysis were described previously [11]. Required integrity of DNA was 400 base pairs.…”
Section: Molecular Studymentioning
confidence: 99%
“…However, recent articles in which larger cohorts of cases were analyzed have described a more variable genetic pattern with multiple losses as well as with multiple gains. In these studies, chromosomal gains were most frequently detected on chromosomes 4, 7, 15, 19, and 20 [8,26,27]. These findings indicate that the molecular-genetic abnormalities in CRCC can encompass a considerably broader spectrum than was previously suggested.…”
Section: Discussionmentioning
confidence: 57%
“…Each slide was independently enumerated by 2 observers (PM and PG). The cut-off values used for each probe were established in a previous study [8].…”
Section: Fluorescence In Situ Hybridization Interpretationmentioning
confidence: 99%